Variable Speed Pump Storage for the Mitigation of SSR in Power System with Wind Generation. (10th December 2019) - Fengchun, Ye; Bitew, Girmaw Teshager; Minxiao, Han; Yao, Sun; Hanhua, Zhang
Abstract : Subsynchronous resonance (SSR) can bring significant negative effects on the grid system like stability, security, and even generator shaft damage. This work presents a new method of using a doubly-fed induction machine (DFIM) based system of variable speed pumped storage plant (VSPS) to mitigate SSR in the power system with high penetration of wind generation. The mitigation is reached based on the principle of balanced shaft mechanical input power and electromagnetic power. The fundamental concepts and phenomena of SSR with wind farm are discussed in brief in this work. For the sake of analysis and verification of performance of the proposed system, the network model including wind farm, VSPS, HVDC, and synchronous machine is built based on Ningxia grid for the SSR study using PSCAD platform. The result shows that VSPS brings significant effect to dampen the SSR in the power system with high penetration of wind generation.